Effect of Frequency of Ejaculation on Semen Characteristics in Two Breeds of Turkeys (Meleagris gallopavo) Raised in a Tropical Environment - Zahraddeen, D.; Butswat, I.S.R.; Kalla, D.J.U.; Sir, S.M.; Bukar, M.T. (International Journal of Poultry Science, 2005)
A study was carried out at the Abubakar Tafawa Balewa University Farm, Bauchi (February - May, 2002) to investigate the effect of frequency of ejaculation (once, twice and thrice per week) on semen traits in exotic and local turkeys. The results showed that ejaculate volume, live spermatozoa, abnormal spermatozoa, sperm concentration and total sperm per ejaculate were significantly (P<0.05) higher in exotic than local turkeys, values being 0.32±0.02 vs 0.17±0.02ml, 83.83±1.33 vs 80.67±1.33%, 11.19±0.73 vs 13.61±0.73%, 4.66±70.73 vs 2.81±74.93 x 109 and 97.72±9.86 vs 50.81±10.45 x 109. It was also shown that sperm concentration was the only variable significantly affected (P<0.05) by frequency of ejaculation. The interaction of breeds and frequency of ejaculation also favoured (P<0.05) the exotic breed at lower frequency of ejaculation. Semen collection in turkeys is more favourable when harvested once per week since semen concentration declines progressively with increase in the ejaculation frequency. The exotic have superior genetic make-up than the local turkeys in terms of their reproductive potential.